Clinical Aspects Of Surgical Suture Material Selection - Mardonov Jamshid Normurotovich; Mahmudov Kodirjon Oltinboevich; Khujamberdiev Abdusalom Ubaydullaevich; Abdullaeva Mokhima Abdullaevna; Nabijonov Bakhodirbek Sodikjon ugli (Academia One, 2025)
Surgical suture material is an integral component of any operative intervention and has a direct impact on the reliability of the formed suture, the course of the wound healing process, and the incidence of postoperative complications [1,3–6]. In modern surgical practice, clinicians are faced with the necessity of selecting from a wide range of suture materials that differ in structure, physicomechanical properties, biocompatibility, and the presence of functional coatings [4,5,18]. The aim of this review is to provide an expanded analysis of the clinically significant properties of various types of surgical suture materials and their role in the development of inflammatory responses, prevention of infectious complications, and optimization of wound healing processes. Based on data from domestic and international literature, the advantages and limitations of mono- and multifilament sutures, absorbable and non-absorbable materials, as well as the potential of antibacterial coatings and physical methods of exposure for improving surgical outcomes are discussed
Keywords: surgical suture material; clinical selection; surgical site infection